Selection of reference genes for quantitative real-time RT-PCR assays in different morphological forms of dimorphic zygomycetous fungus Benjaminiella poitrasii - Pathan, Ejaj K.; Ghormade, Vandana; Deshpande, Mukund V. (Plos One, 2017)
Benjaminiella poitrasii, a dimorphic non-pathogenic zygomycetous fungus, exhibits a morphological yeast (Y) to hypha (H) reversible transition in the vegetative phase, sporangiospores (S) in the asexual phase and zygospores (Z) in the sexual phase. To study the gene expression across these diverse morphological forms, suitable reference genes are required. In the present study, 13 genes viz. ACT, 18S rRNA, eEF1a, eEF-Tu, eIF-1A, Tuba, Tub-b, Ubc, GAPDH, Try, WS-21, NADGDH and NADPGDH were evaluated for their potential as a reference, particularly for studying gene expression during the Y-H reversible transition and also for other asexual and sexual life stages of B. poitrasii. Analysis of RT-qPCR data using geNorm, normFinder and BestKeeper software revealed that genes such as Ubc, 18S rRNA and WS-21 were expressed at constant levels in each given subset of RNA samples from all the morphological phases of B. poitrasii. Therefore, these reference genes can be used to elucidate the role of morpho-genes in B. poitrasii. Further, use of the two most stably expressed genes (Ubc and WS-21) to normalize the expression of the ornithine decarboxylase gene (Bpodc) in different morphological forms of B. poitrasii, generated more reliable results, indicating that our selection of reference genes was appropriate.